2019
DOI: 10.21037/jtd.2019.01.10
|View full text |Cite
|
Sign up to set email alerts
|

One-stage video-assisted thoracic surgery for bilateral multiple pulmonary nodules

Abstract: the clinical effect and the value of applying one-stage VATS for BMPNs. Ultimately, the patients had satisfactory surgical results and recovered well. Methods Inclusive and exclusive criteria of patients Inclusive criteria Patients underwent lung-function testing, bronchoscopy, CT scans, complete blood counts and serum biochemistry tests. Positron emission tomography-CT (PET-CT) was not included as a conventional examination for patients. Their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…Although the trauma of one-stage operation is large and the need to remove more lung tissue, this may increase the potential perioperative risk, but its advantages are also obvious, it can solve the bilateral lesions in one operation, reduce the pain of the patient's secondary surgery, save medical resources, and more importantly, it can reduce the risk of tumor progression caused by staged surgery. Several studies [12][13][14] have shown that simultaneous bilateral VATS is safe and feasible, and does not increase the risk of perioperative surgery. In our study, there were no serious complications and deaths in perioperative period, all patients were discharged smoothly, except for the average operation time compared with unilateral surgery, intraoperative blood loss, postoperative thoracic drainage time and postoperative hospital stay days did not increase significantly, and the results were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the trauma of one-stage operation is large and the need to remove more lung tissue, this may increase the potential perioperative risk, but its advantages are also obvious, it can solve the bilateral lesions in one operation, reduce the pain of the patient's secondary surgery, save medical resources, and more importantly, it can reduce the risk of tumor progression caused by staged surgery. Several studies [12][13][14] have shown that simultaneous bilateral VATS is safe and feasible, and does not increase the risk of perioperative surgery. In our study, there were no serious complications and deaths in perioperative period, all patients were discharged smoothly, except for the average operation time compared with unilateral surgery, intraoperative blood loss, postoperative thoracic drainage time and postoperative hospital stay days did not increase significantly, and the results were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Although one‐stage surgical strategy for bSMPLCs could prevent patients from undergoing a second operation, reduce surgical trauma and hospitalization costs, minimize the risk of tumor progression during two operations and may provide better prognosis, there are still concerns about its perioperative safety. Several studies 6–10,20 have suggested simultaneous bilateral pulmonary resection by video‐assisted thoracoscopic surgery (VATS) is safe and feasible; however, most of those studies were retrospective of small sample size. Atrial fibrillation, pneumonia, persistent air leakage and transient respiratory insufficiency are common postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…For BMPNs that need to be removed, most centers currently perform two‐stage bilateral pulmonary resection with intervals of weeks to months, and believe that perioperative risk of one‐stage surgery is significantly increased. Currently, the data of one‐stage surgical strategy is limited, and safety and effectiveness of simultaneous bilateral pulmonary resection are still controversial 5–10 . In this retrospective cohort study, we report our single‐center experience of simultaneous bilateral pulmonary resection for BMPNs and summarize its perioperative safety.…”
Section: Introductionmentioning
confidence: 98%
“… 6 , 19 Theoretically, single-stage bilateral pulmonary resection also decreases the risk of disease progression, especially in patients with bilateral malignant tumors; shortens the patients’ total hospitalization time; and decreases postoperative complications. 11 13 , 20 Our study indicated that the incidence of unstable hemodynamics may increase in patients undergoing single-stage sequential bilateral VATS if these patients have a lower percent predicted forced vital capacity, longer surgical time, or higher preoperative neutrophil count. Therefore, the preoperative evaluation should be rigorous for patients who are scheduled for single-stage sequential bilateral thoracic surgery.…”
Section: Discussionmentioning
confidence: 83%
“…However, lobectomy and two combined procedures were more frequently performed among patients who underwent two-stage VATS because the patients could recover their pulmonary function after a few months. 13,22 Several published articles comparing different procedures have reported conflicting results, making it difficult to achieve a consensus on which procedure is the best for small pulmonary nodules. 23,24 Our study showed no difference in tumor size, pathologic classification, preoperative chemotherapy, or surgical site in our study.…”
Section: Discussionmentioning
confidence: 99%